PENGEMBANGAN VARIASI PEMANASAN (WARM-UP) BERBASIS PERMAINAN “AGILITY BALL RELAY” UNTUK SISWA - Ashfah Rahmawati; Betty Desi Natalia Sihotang; Cici Pramita Gurning; Dini Al Zahra; Echa Azzahara; Enjel Eonica Br Ginting; Esa Aliza; Ade Ros Riza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a game-based warm-up model called "Agility Ball Relay" as a more engaging dynamic warm-up alternative for elementary school students. The Research and Development (R&D) method, adapted from Borg & Gall's seven-step model, was used to design the initial product, conduct expert validation, and test its effectiveness through limited trials and main trials. Validation by physical education (PJOK) experts and basic motor skills experts resulted in feasibility scores of 86% and 82%, respectively, indicating that the game is safe, appropriate to student characteristics, and feasible to use. Trials on a total of 58 students yielded good implementation and positive responses from teachers and students. Movement activities such as cone drills, high knees, ball rolling, and reactive push-ups have been shown to improve agility, coordination, and physical readiness, making this game effective as a more dynamic, enjoyable, and non-monotonous warm-up variation in PJOK learning.